A Companion to Chaucer. - Brown, Peter (Blackwell companions to literature and culture., 2008)
Designed as both a contribution to original research and as a stimulating and accessible text, this volume is a helpful, reliable, responsive and adaptable resource for students of Chaucer at all levels.